1994
DOI: 10.1128/aem.60.12.4421-4431.1994
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and plasmid diversity within natural populations of Pseudomonas syringae with various exposures to copper and streptomycin bactericides

Abstract: We examined the genetic and plasmid diversity within natural populations of Pseudomonas syringae isolated from three ornamental pear nurseries in eastern Oklahoma. The bactericide spray regimen differed at each nursery; copper and streptomycin, only copper, and no bactericides were applied at nurseries I, II, and III, respectively. Resistance to copper (Cur) and resistance to streptomycin (Smr) were determined for 1,938

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…The incidence of Sm resistance in pathogenic and commensal bacteria in clinical and agricultural habitats is often high and this has most likely been caused by the use of Sm in these environments [3,32,33]. However, the spread and distribution of these genes in pristine habitats, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of Sm resistance in pathogenic and commensal bacteria in clinical and agricultural habitats is often high and this has most likely been caused by the use of Sm in these environments [3,32,33]. However, the spread and distribution of these genes in pristine habitats, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…syringae strains. AP-PCR analysis is a useful tool for distinguishing individual strains within a related taxonomic group and has been used successfully with plant pathogenic bacteria for intrapathovar strain differentiation (Louws et al, 1994;Sundin et al, 1994). In our AP-PCR experiments, DNA fragment patterns were generated, analysed from multiple agarose gels, and a matrix indicating the presence or absence of particular fragments among strains was constructed (data not shown).…”
Section: Uv-b Tolerance Assays Of Phyllosphere Populationsmentioning
confidence: 99%
“…To this reaction mixture, we added approximately 10 6 cells (previously grown on PAF medium for 12 h) with a sterile toothpick, and the mixture was covered with one drop of mineral oil. The amplification cycles, electrophoresis of PCR products and visualization of strain-specific PCR patterns were as described previously (Sundin et al, 1994). The AP-PCR product data were converted into a two-dimensional binary matrix in which 1 indicated that a particular PCR product was present and 0 indicated the absence of a particular PCR product.…”
Section: Arbitrarily Primed Pcr Analysismentioning
confidence: 99%
“…Additionally, plasmids of P. syringae have a mosaic structure and often share extensive regions of similarity, suggesting their evolution through the acquisition and loss of large DNA regions in a multistep process [17-20, 23, 26]. Despite this, plasmid profiles of individual strains appear to be characteristic and stable, although certain plasmids can be lost with high frequency under certain culture conditions [3,[27][28][29][30]. In fact, diverse potential stability determinants were identified among PFP plasmids [18,20,21,[31][32][33], although it is not yet clear whether or not they are functional and what their role in the bacterial life cycle is.…”
Section: Thementioning
confidence: 99%